Equivalent stress-strain law for embedded reinforcements considering bond-slip effects. (15th June 2018) - Díaz de Terán, José Ramón; Haach, Vladimir G.
Highlights: New stress-strain law for embedded reinforcement. This new stress-strain law includes bond-slip effects as defined at Model Code 2010. Comparison of finite element models that consider the new law has been carried out regarding experimental results previously tested in Spain. Results support the use of the new stress-strain law to define the global stiffness of structures with cracking. Abstract: The interaction between steel reinforcement and concrete must be always considered to well describe and predict the behavior of reinforced concrete (RC) structures. A common way to model RC is by embedded reinforcements in finite element models. Embedded reinforcement implies that bond conditions between steel and concrete are perfect so, in order to consider bond-slip effects, stress-strain law of steel may be modified. Previous researches proposed modified stress-strain laws of steel bars by considering a constant equivalent stiffness value and reducing the yield strength of steel. This paper aims to show a way to generate a non-linear equivalent stress-strain law for embedded reinforcement bars. This modified non-linear law is based on the bond-slip model provided by Model Code. After proposing this embedded reinforcement model, this paper compares global deflection of slabs that were tested in Spain with the deflection results that are predicted with the new stress-strain law using the software DIANA®. The conclusion is that this new model can be used to predict global behavior of RC structures by finite element models.